Effect of thermocycling to adhesive interface of enamel analyzed by polarized light microscopy - Gonçalves, Rafael Simões; da Silva, Naiara Montes; Watanabe, Mauricio Umeno; Shinohara, Mirela Sanae (Brazilian Dental Science, 2016)
Objective: The less aggressive demineralization of enamel by self-etching systems results in greater staining, marginal leakage, and failure in their restorations, so this study aimed to assess the silver nitrate infiltration and tag formation of the enamel/adhesive interface. Material and Methods: Two hundred enamel fragments were randomly assigned into 10 groups according to the adhesive system (Single Bond Adper Plus-(SB), Clearfil Tri-S Bond-(CF), or Scotchbond Universal-(SBU)) and enamel surface (ground-(ge), unground-(ue), phosphoric acid etching-(pha), or none) (n=10): (SB-ue), (SB-ge), (CF-ue), (CF-ge), (CF-ue/pha), (CF-ge/pha), (SBU-ue), (SBU-ge), (SBU-ue/pha), and (SBU-ge/pha). Half of the restored samples were submitted to thermocycling. Four slices of 1.0mm/sample were obtained to evaluate tag formation and silver nitrate infiltration. All of the specimens were examined with Polarized Light Microscopy, and the percentage of infiltration was quantified. Results: No interactions were found among the three factors. The adhesive and aging exhibited an interaction. Significant differences were found only after thermocycling: the SB and SBU-etched groups had decreased infiltration compared with the other groups. The tag length after etching was higher for ge compared with ue, regardless of the adhesive system. Conclusion: The self-etching techniques resulted in significantly less tag formation compared with the conventional technique.KeywordsAdhesives; Aging; Dental enamel; Microscopy, polarization; Silver nitrate.